Locoregional Radiotherapy in Patients with Advanced Breast Cancer Treated with Cyclin-Dependent Kinase 4/6 Inhibitors Based on Real-World Data - Marcin Kubeczko; Dorota Gabryś; Anna Polakiewicz-Gilowska; Barbara Bobek-Billewicz; Michał Jarząb (MDPI AG, 2024)
Background. The use of locoregional radiotherapy (RT) in patients with advanced ER-positive, HER2-negative breast cancer remains a topic of ongoing debate. In this study, we aimed to evaluate the efficacy of locoregional RT in advanced breast cancer patients treated with cyclin-dependent kinase 4/6 inhibitors (CDK4/6i) in a first-line setting. Methods. We conducted a retrospective analysis of patients diagnosed with advanced breast cancer between 2018 and 2023 who received treatment with CDK4/6i and underwent locoregional radiotherapy. Results. Among the 371 patients treated with CDK4/6i as part of their first-line therapy, 23 received locoregional RT either concurrently or sequentially with CDK4/6 inhibitors. Disease progression within the breast occurred in 19 patients (5.1%). Among these cases, five patients had previously undergone breast RT (5/23, 21.7%), while 14 did not (14/348, 4.0%, p = 0.004). All cases of local progression after RT followed palliative doses and were accompanied by early systemic progression. The 2-year PFS in the entire cohort of patients treated with locoregional RT was 65.7% (95% CI: 40.5-82.3%). Notably, patients who received higher RT doses had longer 2-year PFS (83.3%, 95% CI: 27.3-97.5%) than those with palliative RT doses (59.3%, 95% CI: 30.7-79.3%); however, the results were not statistically significant (p = 0.58). Furthermore, the 2-year local control in the entire cohort with locoregional RT was 73.0% (95% CI: 46.5-87.9%). Importantly, no local progression was observed after RT when using high doses. Conclusions. The addition of locoregional radiotherapy to first-line CDK4/6 inhibitors warrants further investigation across various clinical scenarios in advanced breast cancer. Palliative radiation regimens delivered early in breast oligoprogression may not always suffice, emphasizing the need for comprehensive studies in this context.